Learning and teaching French reading for main ideas by using KWL-PLUS technique for year 2 French students, 12+4 system at Luang Prabang Teacher Training College - HATSADY, Soudachanh (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
The purposes of this research were to: 1) study the efficiency of the learning and teaching French reading for main ideas by using KWL-PLUS technique for year 2 students, 12+4 system Luang Prabang Teacher Training College based on the performance criteria of 80/80; 2) study the effectiveness of the learning and teaching French reading for main ideas by using KWL-PLUS technique for year 2 students; and 3) study the students’ satisfaction with learning and teaching French reading for main ideas by using KWL- PLUS technique for year 2 students. The sample group was the students majoring in French language with the total number of 14 chosen by purposive random sampling. The research instruments were 4 lesson plans, 4 French reading for main idea tests from each lesson, and the students’ satisfaction questionnaire. The data were analysed by mean and standard division. The results showed as follows: 1) The efficiency of the learning and teaching French reading for main ideas by using KWL-PLUS technique for year 2 students, 12+4 system LuangPrabang Teacher Training College was 80.54/81.79, which was higher than the performance criteria 80/80. 2) The effectiveness of the learning and teaching French reading for main ideas by using KWL-PLUS technique was 0.64. 3) The students’ satisfaction with learning and teaching French reading for main ideas by using KWL-PLUS technique was at a higher level with = 4.52 and S.D =1.11. The purposes of this research were to: 1) study the efficiency of the learning and teaching French reading for main ideas by using KWL-PLUS technique for year 2 students, 12+4 system Luang Prabang Teacher Training College based on the performance criteria of 80/80; 2) study the effectiveness of the learning and teaching French reading for main ideas by using KWL-PLUS technique for year 2 students; and 3) study the students’ satisfaction with learning and teaching French reading for main ideas by using KWL- PLUS technique for year 2 students. The sample group was the students majoring in French language with the total number of 14 chosen by purposive random sampling. The research instruments were 4 lesson plans, 4 French reading for main idea tests from each lesson, and the students’ satisfaction questionnaire. The data were analysed by mean and standard division. The results showed as follows: 1) The efficiency of the learning and teaching French reading for main ideas by using KWL-PLUS technique for year 2 students, 12+4 system LuangPrabang Teacher Training College was 80.54/81.79, which was higher than the performance criteria 80/80. 2) The effectiveness of the learning and teaching French reading for main ideas by using KWL-PLUS technique was 0.64. 3) The students’ satisfaction with learning and teaching French reading for main ideas by using KWL-PLUS technique was at a higher level with = 4.52 and S.D =1.11.